Ultimates - Neville, Robert C. (Albany, NY : State University of New York Press, 2013)
"A new theology of ultimate reality and a new theory of religion to back it up addressed to believers and scholars of all traditions"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Philosophical theology; Philosophy and religion; RELIGION / Philosophy; Electronic books